O uso do brincar na clínica com ciranças autistas - Mello, Ingrid Coelho Sales de (2015)
This work is the product of some reflections originated during a period of work in some CAPS in the city of Campina Grande / PB, in which calls were made in group and individual with autistic children. From this experience, became interested in researching the relational space in these meetings and the possibilities for interaction between children with autism and the other. An important aspect in this period I participated in these activities CAPS, was observed using these autistic children were the experience of playing, awakening my interest in researching what happens in this phenomenon, and that you can think of it as a device favoring the intermediary between the child and others. Winnicott points out that the play is an elaborate activity that enables the creation of externality with condition for creative living, which develops thinking, knowing and learning in a meaningful way, and playing you learn to transform and use the objects the world for it to carry out and sign the gestures themselves, creating their own subjectivity. Thus, issues related to autism and the play were discussed in this paper, considering the importance of the mother-infant relationship, understanding that a failure in this regard might cause difficulties in her maturing process. It was in this context that the work aimed to study the use of play in respect of the autistic child with the other. This was a qualitative research study, which used the theoretical framework of psychoanalytic theory, particularly Winnicott, about autism and about the play, provided the cornerstones. Some discussions were held, from service to autistic children memories in the context of CAPS, as an illustration to the debate about play therapy in these children. At the end of work, it was found that the play allows the child to unravel a world beyond itself, facilitating psychotherapeutic work and the interpersonal relationship with each other and functioning as a useful therapeutic device.